West Indian Drywood Termite Cryptotermes brevis (Walker) (Insecta: Isoptera: Kalotermitidae) - Johnalyn M. Gordon; Rudolf H. Scheffrahn; Nan-Yao Su (EDIS, 2021)
Contents: Introduction - Distribution - Description and Identification - Life History - Damage - Pest Status - Management - Selected References.